Large variation in measures used to assess outcomes of opioid dependence treatment: A systematic review of longitudinal observational studies. (2nd October 2017) - Wiessing, Lucas; Ferri, Marica; Darke, Shane; Simon, Roland; Griffiths, Paul
Abstract: Issues: Treatment outcomes for drug users are critical for informing policy and therapeutic practice. The coherence of outcomes, changes and drug use measures from observational studies on opioid use treatment were reviewed. Approach: Systematic review of the literature for longitudinal observational studies, from 1980 through November 2015, in all languages, with data on treated opioid users, using Pubmed, the Cochrane Library and additional strategies (e.g. Pubmed function 'related citations' and checking reference lists of eligible studies). Key Findings: Twenty‐seven studies were included (11 countries, 85 publications, recruitment 1962–2009). Baseline n was >65 686 and median follow‐up 34.5 months (21 studies) or 51.4 person‐months (10 studies). Eight outcome domains were identified: 'drug use' (21/27 studies), 'crime' (13), 'health' (13), 'treatment‐related' outcomes (16), 'social functioning' (13), 'harms' (8), 'mortality' (13) and 'economic estimates' (2 studies). All studies using drug use outcomes included a binary (abstinence) category in at least one measure. Studies typically reported outcomes on less than half (on average 3.7 or 46%) of the eight outcome domains, while the average was 5.1 (64%) in seven studies initiated since 2000. Implications and Conclusion: Wide variation exists in outcome measures found in longitudinal observational studies of treatment of opioid users. This reduces replicability of studies and suggests a lack of common expectations on treatment success. Future studies should consider using all or most of eight outcome domains identified (excluding economic analyses if unfeasible), non‐binary measures and amount/value of drugs used and consensus meetings with joint ownership of scientific, treatment and patient communities.